Effects of the COVID-19 pandemic on patients with NMO spectrum disorders and MOG-antibody-associated diseases: COPANMO(G)-study - Hümmert, Martin W.; Jarius, Sven; Wildemann, Brigitte (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2023)
To evaluate the effects of the coronavirus disease 2019 (COVID-19) pandemic on the life of patients with neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated diseases (MOGAD).